A Comparitive Study of Subject Knowledge of B.Ed Graduates of Formal and Non-Formal Teacher Education Systems - Perveen Saif; Amjad Reba; Jalal ud Din (Journal of Education and Educational Development, 2020)
This study was designed to compare the subject knowledge of B.Ed graduates of formal and non-formal teacher education systems. The population of the study included all teachers from Girls High and Higher Secondary Schools both from private and public sectors from the district of Peshawar. Out of the total population, twenty schools were randomly selected from which 60 teachers from formal and 60 from non-formal system (6 teachers from each school) were randomly selected. A test was prepared and personally distributed among 120 teachers. The data were organized and analyzed through descriptive analysis. It was found that B.Ed. graduates from formal system had more subject knowledge as compared to B.Ed. graduates from non-formal teacher education system. It is recommended that the graduates as well as the teacher educators need to update their knowledge and work for continuous professional development.
Keywords: distance learning; formal and non-formal teacher education system